2010
DOI: 10.1007/s12195-010-0109-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomechanics: The Molecular Basis of How Forces Regulate Cellular Function

Abstract: Recent advances have led to the emergence of molecular biomechanics as an essential element of modern biology. These efforts focus on theoretical and experimental studies of the mechanics of proteins and nucleic acids, and the understanding of the molecular mechanisms of stress transmission, mechanosensing and mechanotransduction in living cells. In particular, singlemolecule biomechanics studies of proteins and DNA, and mechanochemical coupling in biomolecular motors have demonstrated the critical importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 94 publications
(93 reference statements)
0
30
0
Order By: Relevance
“…These changes may allow the signaling molecules to bind the force-sensing molecules to elicit the biochemical signals involved in the cellular responses to the matrix rigidity (45). Shp2…”
Section: Discussionmentioning
confidence: 99%
“…These changes may allow the signaling molecules to bind the force-sensing molecules to elicit the biochemical signals involved in the cellular responses to the matrix rigidity (45). Shp2…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been an incredible focus on cell mechanosensing: the ability of cells to sense and respond to the mechanical properties of their surroundings 19 . Studies have demonstrated that cell mechanosensing can have profound effects on cell fate, cell survival and cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…At the focal adhesion, actin filaments of the cellular cytoskeleton are linked to the extra-cellular membrane (ECM) of the substrate [5]. Once linked, both mechanical forces [11] originating from within the cell – such as myosin induced contraction of the actin filaments [12] during cell migration – can act on the ECM and the substrate, and, mechanical forces originating from outside the cell – such as flow induced cyclic stress in the case of endothelial cells [13] – can be transduced to the cellular machinery [14].…”
Section: Introductionmentioning
confidence: 99%